Vreme beds and the genesis of the karst caves in them in wider surroudings of Škocjanske jame (Škocjanske jame caves, Slovenia) - Knez, Martin (Acta carsologica, 1995)
The Vreme beds (Maastrichtian) are composed mainly of dark thin bedded, sometimes strongly bituminous limestones and rarely markly limestones and coalshales and inliers of the coal. According to structure the limestone is biomicrite of wackstone-packstone type. Among the mentioned beds there are the most probably the syngenetic breccias too. Fossil remains and sedimentological data show that the mayor part of the Vreme beds was deposited in a shallow sea. On the treated area there are in Vreme beds 6,2% of all the caves only, or 0,3 cave/km2 respectively, which means two thirds bellow the average
Keywords: kras (geologija); krasoslovje; kraške jame; List of caves in Slovenia; speleologija; Škocjan Caves; Škocjanske jame